Messages : free expression, media and the west from Gutenberg to Google - Winston, Brian (Routledge, 2005)
Easy to read, and highly topical, Messages writes a history of mass communication in Europe and its outreaches, as a search for the origins of media forms from print and stage, to photography, film and broadcasting. Arguing that the development of the mass media has been an essential engine driving the western concept of an individual, Brian Winston examines how the right of free expression is under attack, and how the roots of media expression need to be recalled to make a case for the media's importance for the protection of individual liberty. Relating.